Prevalence of Burnout Syndrome Among Medical Students - Novitasari, Andra (Universitas Gadjah Mada, 2024)
Background: The mental health of medical students is a matter of concern due to the heavy study load that begins with the bachelor’s degree program, progresses through the professional phase, and continues into the internship period. Approximately 49% of medical students in the USA and between 28%-61% in Australia experience burnout. Potential factors such as responsibilities for completing assignments, parental expectations, efforts to maintain grades, and academic competition can lead to burnout syndrome. If individuals are unable to adapt to and manage prolonged stress, it can result in maladaptive behavior.Aims: The purpose of this research was to assess the prevalence and severity of burnout syndrome among medical students at the University of Muhammadiyah Semarang.Methods: A descriptive analysis was conducted using primary data collected through the Maslach Burnout Syndrome Inventory. A total sampling technique was used with respondents from the medical professional study program during the 2022-2023 academic year. Those with psychiatric disorders, consuming sedatives, or absent during the study period were excluded.Results: Out of 135 participants, the incidence of burnout syndrome showed that 77.0% experienced low emotional exhaustion, 11.9% moderate, and 11.1% high. Depersonalization cases were 80.7% low, 9.6% moderate, and 9.6% high. Personal accomplishment was reported as 37.0% low, 17.0% moderate, and 45.9% high.Conclusion: The incidence of burnout syndrome among the respondents predominantly featured low in emotional exhaustion and depersonalization, and high personal achievement. Keywords: burnout syndrome, depersonalization, emotional exhaustion, medical student, personal accomplishment